The type craetive industrialists in the conceptual age - Ab. Aziz Shuaib; Nasirin Abdillah (Universiti Malaysia Kelantan, 2014)
We are now in the conceptual age. The economy and society built on the logical order of the information age are now nurtured to fulfil the emotional and perceptual world. Globalisation has further magnified such phenomenon as it encroaches on the conceptual age. Consequently, today’s consumers demand to be treated as individuals – they want products that make them feel right instead of products that can just do the right thing for them. In conjunction with this, it is now imperative that creative workers need to change their mind-sets so as to enhance their innovative and creative skills in line with the demands of the conceptual age. This paper aims at providing a general overview of the development and design trend, illuminating on the characteristics of creative workers required in the creative economy and proposing types of trainings needed to enhance their innovative and creative skills for creative industries.